Urban greenery management and energy planning: A GIS-based potential evaluation of pruning by-products for energy application for the city of Milan. (November 2020) - Ferla, G.; Caputo, P.; Colaninno, N.; Morello, E.
Abstract: The present paper concerns the assessment of biomass by-products from the urban greenery maintenance with an energy perspective. Usually pruning is not organized by a consolidated planning practice, mainly because of lack of information. After estimating the quantity of wood pruning by-products by means of dendrometric equations and the availability of information on current greenery management, an innovative GIS-based method was implemented and tested on Milan, in northern Italy. The main outcome is the quantification of the energy potential in terms of available wood biomass, displayed on a geo-referred urban map. Moreover, the outcomes of the research could support the administrations in improving the management of these materials otherwise wasted and therefore in converting public expenses for maintenance into public profits available for further investments. On the energy supply side, the GIS database could support the local matching between available renewable sources and energy supply systems in operation (i.e. local district heating and cogenerative systems), providing a low-range and cost-effective renewable resource, also enhancing circular economy at the local scale. Highlights: A novel method for an effective urban greenery management is proposed and analysed. Dendrometric equations and a GIS were combined for pruning by-products estimation. The urban greenery of Milan was considered as case study. A biomass PE potential between 26 and 76 GWh was assessed for the case study. The use of pruning by-products in a biomass district heating plant is evaluated.